The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/14786435.2013.782443
|View full text |Cite
|
Sign up to set email alerts
|

Finite element simulation of the magneto-mechanical response of a magnetic shape memory alloy sample

Abstract: In this paper, the stress-and magnetic field-induced variant reorientation in a magnetic shape memory alloy (MSMA) sample is simulated by using the finite element method. This model is set up based on a three-dimensional setting with the whole sample and the surrounding space taken into account. A typical loading pattern is proposed on the sample. The unknowns of the model governing system include the spatial displacement vector, the scalar magnetic potential and some internal variables related to the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Additionally, all three possible crystal orientations are taken into account instead of the two-dimensional simplification. [10] gives a more comprehensive overview of the different models available.…”
Section: Ferroelectric Materialsmentioning
confidence: 99%
“…Additionally, all three possible crystal orientations are taken into account instead of the two-dimensional simplification. [10] gives a more comprehensive overview of the different models available.…”
Section: Ferroelectric Materialsmentioning
confidence: 99%
“…The governing PDE system of the current model can be explicitly solved by using an iterative numerical algorithm [4]. To show the validity of the current model, we consider a MSMA sample with cuboid shape and subject to perpendicularly applied magnetic and mechanical loadings (cf.…”
Section: Example Of Numerical Simulationmentioning
confidence: 99%
“…Phenomenological models have been developed to predict macroscopic behaviors of MSM alloys based on the idea of moving TBs as well as domain wall boundaries. In many cases that is done by introducing internal variables that describe alloy microstructures: the volume ratio of different variants, the volume ratio of the magnetic domains, and the orientations of the magnetization vectors [31], [32], [33], [34], [35], [36], [37]. Many of these models were successfully implemented using numerical finite element techniques [34], [37], [38], including non-conventional ones, such as the absolute nodal coordinate formulation [39].A development of the model to study the quasi-static movement of TBs based on internal variables was reported in [40], and recent work [41] presents a numerical algorithm for studying the dynamic magnetomechanical response of MSM alloys.…”
Section: Introductionmentioning
confidence: 99%